Prostatic Abscess after Stapled Hemorrhoidopexy Caused by ESBL Extended Spectrum Beta Lactamase Producing Klebsiella pneumoniae: An Additional Challenge to Postoperative Sepsis. (17th July 2017) - Saleh, Asem; Kibeida, Abdelnasir; Amin, Elsaid; Khalil, Abdalla; Abu Shakra, Rafat; Elwakil, Mohamed
Abstract : Postoperative septic complications of hemorrhoids surgical interventions are rare, but very serious with high mortality rate. Early diagnosis and prompt therapy are essential to save patient's life. There are a good number of articles and case reports about these septic complications. We are presenting a case report of a prostatic abscess caused by extended spectrum beta lactamase (ESBL) producing Klebsiella pneumoniae after hemorrhoidopexy. Our patient was a healthy middle aged Saudi male who has no significant medical history apart from morbid obesity and recurrent urinary tract infections. ESBL producing K. pneumoniae could be detected only after aspiration of the prostatic abscess, but proper antibiotic was introduced intravenously on admission before culture of aspirate of the abscess was available. Antibiotic was continued for 30 days and abscess resolved completely. In our electronic search, we could not find any case report of prostatic abscess after stapled hemorrhoidopexy caused by ESBL producing organism. This is an additional challenge for treating physicians as these organisms are sensitive only to one group of antibiotics (carbapenem group).